2002
DOI: 10.14356/kona.2002009
|View full text |Cite
|
Sign up to set email alerts
|

A Century of Research in Sedimentation and Thickening

Abstract: This paper provides a concise review of the contributions to research in sedimentation and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 98 publications
1
36
0
Order By: Relevance
“…16 However, for monodisperse suspensions, in which the maximum volume fraction is not one, Richardson-Zaki power-law expressions can become inaccurate by allowing unphysical volume fractions. 17 Alternatively, particle hindrance can be taken into account by using a relationship based on a suspension viscosity model. 18 Using a suspension viscosity model has the advantage of reducing the sedimentation velocity to zero at the maximum volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, for monodisperse suspensions, in which the maximum volume fraction is not one, Richardson-Zaki power-law expressions can become inaccurate by allowing unphysical volume fractions. 17 Alternatively, particle hindrance can be taken into account by using a relationship based on a suspension viscosity model. 18 Using a suspension viscosity model has the advantage of reducing the sedimentation velocity to zero at the maximum volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] provide answers. For reviews of the development of that particular branch of fluid mechanics, the reader is referred to [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed review on cohesive particles is beyond the scope of this manuscript, however, for further readings on the subject the authors recommend the following works found in the literature (Concha & Bürger, 2002;Kusuda et al, 2007;Mantovanelli & Ridd, 2006;Bürger & Wendland, 2001;Garrido, Bürger & Concha, 2000). Most studies in the literature are related to the description of tidal and marine sediments.…”
Section: Semi-empirical Modelmentioning
confidence: 99%